PENERAPAN MODEL INVENTORI PROBABILISTIK FUZZY MULTIOBJEKTIF PADA SISTEM PERSEDIAAN BUAH SALAK - DEWI, NOVI RUSTIANA; SUSANTI, EKA; ZAYANTI, DES ALWINE; INDRAWATI, INDRAWATI; DWIPURWANI, OKI; MUNAWAROH, SITI NATASYA (E-Jurnal Matematika; Vol 13 No 1 (2024), 2024)
Inventory control is very important in production and trading activities. The purpose of inventory control is to maintain product availability. In certain cases, the products provided must be ordered from distributors outside the city and require waiting time from the time the order is placed until the product is received. The Multiobjective Probabilistic Fuzzy Inventory model can be applied to inventory optimization problems with the uncertainty of the leadtime parameter. In this study, the model was applied to the problem of supply salak fruit at one of the distributors. The first objective function is to minimize holding costs and the second is to minimize deterioration costs. The inventory model is transformed into a single objective form using a weighted method. Based on the results, the order cycle time is 3 days with the optimal total inventory of 430.1086 kg. The holding cost and deterioration costs are IDR 2,075,866 and IDR 571,034, respectively. Changes in the weight value of the objective function result in changes in the total cost value. The greater the weight for the first objective function, the smaller the total cost.